Obestatin improves oxidative brain damage and memory dysfunction in rats induced with an epileptic seizure - YEGEN, BERRAK; YILDIRIM, ÇAĞAN; AKAKIN, DİLEK; YÜKSEL, MERAL; KOYUNCUOĞLU, TÜRKAN (ELSEVIER SCIENCE INC, 2017)
Obestatin was shown to alleviate renal, gastrointestinal and haemorrhage-induced brain injury in rats. In order to investigate the neuroprotective effects of obestatin on seizure-induced oxidative brain injury, an epileptic seizure was induced with a single intraperitoneal (i.p.) close of pentylenetetrazole (PTZ, 45 mg/kg) in male Wistar rats. Thirty minutes before the PTZ injection, rats were treated with either saline or obestatin (1 mu g/kg, i.p.). Seizure was video-taped and then evaluated by using Racine's scoring (0-5). For the assessment of memory function, passive-avoidance test was performed before seizure induction, which was repeated on the 3rd day of seizure. The rats were decapitated at the 24th or 72nd hour of seizures and brain tissues were obtained for histopathological examination and for measuring levels of malondialdehyde (MDA), glutathione (GSH), reactive oxygen radicals and myeloperoxidase (MPO) activity. Obestatin treatment reduced the average seizure score, decreased the occurrence and duration of generalized tonic-clonic seizures, presenting with a shorter latency to their onset. Increased lipid peroxidation and enhanced generation of oxygen-derived radicals detected at the post-seizure 72nd h were suppressed by the consecutive treatments of obestatin, but no changes were observed by the single obestatin treatment in the 24-h seizure group. Neuronal damage and increased GFAP immunoreactivity, observed in the hippocampal areas and cortex of PTZ-induced rats were alleviated in 3-day obestatin-treated PTZ group. PTZ-induced memory dysfunction was significantly improved in obestatin-treated PTZ group as compared to saline-treated rats. The present data indicate that obestatin ameliorated the severity of PTZ-induced seizures, improved memory dysfunction and reduced neuronal damage by limiting oxidative damage. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Seizure; Oxidative stress; Obestatin; Memory dysfunction; PENTYLENETETRAZOLE-INDUCED SEIZURES; COGNITIVE IMPAIRMENT; GHRELIN; RECEPTOR; INJURY; MYELOPEROXIDASE; ANTIOXIDANT; STRESS; EPILEPTOGENESIS; EXPRESSION